Kajian Peraturan Kepala Badan Pengembangan Sumber Daya Manusia Perhubungan Nomor : PK.16/BPSDMP-2017 tentang Pedoman Standarisasi Penyelenggaraan Simulator - Mudiyanto Mudiyanto; Djamaludin Malik; Dwiyono Soewono (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
The 2010 Manila amendment STCW Convention had a major update with a greater focus on technical skills called non-technical skills. Technical skills are related to handling ship equipment, while non-technical skills are often described as cognitive and communicative skills. The aim of this study was to investigate the role of instruction and assessment for developing students' professional competence in a simulation-based learning environment. This analysis draws on ethnographic fieldwork and detailed interaction analysis of videotape data from simulator training sessions in navigation courses by examining how maritime instructors utilize simulator technology for teaching and formative assessment to develop students' professional competencies. The results of this study emphasize the importance of systematic professional guidance and feedback in simulator-based training in accordance with the Regulation of the Head of Agency and Development of Human Resources for Transportation Number pk.16/BPSDMP-2017 Regarding Guidelines for Standardization of Operation Simulators.